Windhoek - Eine stadtgeographische Skizze - Bähr, Jürgen (ERDKUNDE, 1970)
Before it was occupied by German troops, Windhoek was only a periodic settlement of a few indigenous families and the mission. Because of the favourable geographical location on the only route linking the northern and southern parts of the country the German government established a garrison in 1890. While the period up to the First World War - interrupted only by native uprisings - was a time of growth and expansion for the town, the poor economic situation and political instability between the wars led to stagnation in the development of Windhoek. A second phase of growth began only after 1950, stimulated by the switching of economic emphasis to trade, commerce, mining and industry and the improvement of road links to other parts of the country. The strong areal expansion of the town was accompanied by a surge in population from 20 598 (1951) to 67100 (1968). However, white inhabitants in Windhoek still outnumber the indigenous and coloured population. While in the inner city only the separate entrances in all public buildings hint at the fact that the co-existence of white and black is regulated by precise ordinances and laws, the new residential areas outside the centre for indigenous and coloured people are, under the principles of the apartheid policy, fully separated from those of the whites. In contrast to the one-sided facilities of the service centres in the farm zone of South West Africa, the capital is marked by a multiplicity of functions: Windhoek is the seat of the most important organs of administration, the distribution and delivery point for the whole country of many essential commodities. Part of the farm production of the immediate area is processed in the dairy or the preserves plant. The specialist shops and department stores of the town offer the visitor better shopping possibilities and a wider choice than in the small country settlements and Windhoek is the dominant centre for the provision of social and cultural needs for all the inhabitants of South West Africa.